EL LOCO, EL MONÓMANO Y EL IDIOTA EN LOS CUENTOS DE NODIER - Andrade Boué, Pilar (Anales de Filología Francesa, 2007)
This work analizes the character of the fool in Charles Nodier’s fantastic tales. The author tries to establish the causes, morphology and posterity of madness in this romantic writer.